2016
DOI: 10.1007/s00170-016-8867-y
|View full text |Cite
|
Sign up to set email alerts
|

Study on the burning loss of magnesium in fiber laser welding of an Al-Mg alloy by optical emission spectroscopy

Abstract: In order to study the burning loss of magnesium, a specially designed device was used to capture the spectrum emitted from the keyhole plasma in deep penetration laser welding of aluminum alloy 5052. The content of magnesium in the weld bead was measured by an electron probe microanalyzer (EPMA). The effect of the welding parameters on the spectral intensity of magnesium plasma was examined, and the distributions of the spectral intensity of magnesium plasma in the radial and depth directions of the keyhole we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Zhou et al . (2017) conducted spectroscopic analysis to quantify the composition of metal vapor in laser welding of A5052, and the results indicated that a large amount of Mg was evaporated during the welding process 29 . This research supports our finding that the element with boiling temperature lower than that of aluminum plays a significant role on keyhole formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al . (2017) conducted spectroscopic analysis to quantify the composition of metal vapor in laser welding of A5052, and the results indicated that a large amount of Mg was evaporated during the welding process 29 . This research supports our finding that the element with boiling temperature lower than that of aluminum plays a significant role on keyhole formation.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have focused on the weld quality in laser welding of various series of aluminum alloys by both experiments and simulations 27 29 . These previous researches showed that the aluminum alloy with different compositions had different weldability, which was caused by the differences in weld pool behavior.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 5a, some gas pores were observed in the weld zone. Unlike that of arc welding, the gas-pore formation of laser welding may be due to the trapping of metal vapor because of the higher power density used for laser welding [26][27][28]. EDS analysis indicated that the weld Al content (8.00 wt %) was reduced compared with the base metal (13.26 wt %), and the Al content (9.62 wt %) of gas pore wall was higher than that of weld, as shown in Figure 5b and Tables 1 and 3.…”
Section: Microstructures Of Laser-welded Jointsmentioning
confidence: 99%
“…Laser Welding has been considered as one of the best welding processes for titanium alloys because of its high energy density, fast welding speed, small weld deformation, and flexible operating [1][2][3]. However, in this process, burning loss of some solute elements caused by the high laser intensity (10 6 W/cm 2 ) may reduce joint performance [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…When the high-energy laser beam focuses on the surface of the base metal, the keyhole is formed within a very short time, and the temperature is even higher than the boiling point of the base metal. Large amounts of vaporization of low-boiling alloy elements occur frequently, and the flow of molten pool would aggravate the burning loss [6] of alloy elements, which will result in the severe inhomogeneity of chemical composition around the weld [4,7]. The inhomogeneity may subsequently cause the microstructure transformation nonuniformity and ultimately affect the mechanical properties of the welded joints [8,9].…”
Section: Introductionmentioning
confidence: 99%